2009
DOI: 10.1176/jnp.2009.21.4.413
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, Depression, and Quality of Life in Parkinson’s Disease

Abstract: Parkinson's disease has a major impact on quality of life. This cross-sectional study assessed 43 idiopathic Parkinson's disease patients in order to evaluate the impact of Parkinson's disease severity (Hoehn and Yahr scale), anxiety, and depression (Hospital Anxiety and Depression Scale) on quality of life (Short Form-36 Health Survey questionnaire). Hospital Anxiety and Depression Scale and Short Form-36 Health Survey scores were significantly correlated in Hoehn and Yahr stage 2 Parkinson's disease (n=33), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(37 citation statements)
references
References 23 publications
3
25
0
9
Order By: Relevance
“…A recent systematic review concluded that depression, disease severity and disability negatively influence the patient-reported impact of PD and thus determined depression to be an important predictor of QOL (36). Similar results have been reported for anxiety (3)(4)(5); however, with insufficient supporting data (37). Many studies have heretofore focused on the impact of depression and motor disability on poor life quality while neglecting to examine the role of anxiety.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…A recent systematic review concluded that depression, disease severity and disability negatively influence the patient-reported impact of PD and thus determined depression to be an important predictor of QOL (36). Similar results have been reported for anxiety (3)(4)(5); however, with insufficient supporting data (37). Many studies have heretofore focused on the impact of depression and motor disability on poor life quality while neglecting to examine the role of anxiety.…”
Section: Discussionmentioning
confidence: 71%
“…Quelhas et al (4) also showed anxiety to be the strongest predictor of QOL. Further research is necessary to address this issue since these studies dealt with a small number of patients, used a generic measure for QOL (the Short Form-36 Health Survey questionnaire) and excluded specific aspects of PD management such as iatrogenic symptoms (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found a strong relationship between cognitive and affective symptomatology in PD and decreased QoL [5,52,53,54], as well as impairment of everyday functioning [7,55]. Therefore, identifying neuropsychological impairments in EOPD should be important to clinicians to provide a more comprehensive treatment that includes multidisciplinary interventions.…”
Section: Discussionmentioning
confidence: 99%
“…12 Many studies report comparable effects of depression and anxiety on quality of life, but at least one suggested that anxiety may be the strongest predictor of quality of life in PD. 13 In addition, psychiatric symptoms contribute significantly to level of caregiver burden and distress. [14][15][16] One study found that the greatest predictor of caregiver-endorsed depressive symptomology on the Geriatric Depression Scale (GDS) was the cared-for patient's GDS score, 17 suggesting that depressive symptoms in PD patients predict depressive symptoms in their spouses, arguably leading to overall greater health-care burden and cost.…”
Section: Impactmentioning
confidence: 99%